Sacred narratives: spiritual autobiographies of women as intercultural practice - Cheuquenao Aillapan, Rosa Persida (2021)
The recognition of women’s spirituality as a sphere of denial and as an exercise that would allow an interspiritual dialogue through the autobiographies of the authors was analyzed. Based on antecedents on the recognition of the spirituality of women, a qualitative research with a narrative biographical design was carried out. The results showed that the recognition of the spirituality of women is part of a critical and decolonial interculturality and that spiritual autobiography would be an instrument of dialogue between spiritualities. It is concluded that the spirituality of the outdoors would make the intercultural recognition process possible.